KAJIAN YURIDIS KONVERSI SERTIFIKAT HAK GUNA BANGUNAN MENJADI SERTIFIKAT HAK MILIK OLEH YAYASAN - Sunyoto Sunyoto; Nynda Fatmawati Octarina (Jurnal Ilmiah Advokasi, 2023)
Foundations that have ownership rights over land, as long as the land is used for businesses in the religious and social fields, can only be used in accordance with the nature of the legal entity. (Article 49 paragraphs (1) and (2) of the BAL). The research method in this writing is using normative juridical research methods. The approach was carried out using an analytical descriptive analysis method regarding the juridical study of the conversion of SHGB to SHM by the foundation. The technique of collecting legal materials is carried out through literature studies and analysis, as well as studies of searching internet materials in the form of scientific articles and journals related to this research. Furthermore, it was analyzed using descriptive analytical techniques and was critical of the object of discussion of the juridical study of the conversion of SHGB to SHM by the foundation. The conversion of SHGB land rights to SHM according to the Decree of the State Minister for Agrarian Affairs/Head of BPN No. 6 of 1998, only regulates the increase in land rights to land and buildings specifically for residential homes. In order to be able to convert land rights, foundations must first obtain a Decree on the Appointment of a Legal Entity that can have Ownership Rights over Land issued by the Head of the BPN (Article 10 paragraph (1) letter b PMNA/KBPN Number 9 of 1999).Keywords: Juridical Study; Conversion of SHGB to SHM; Foundation.